Controlling the Inventory of Boiler Ash Raw Materials in Organic Fertilizer Using the Minmax Method (Case Study: UMTR Belilas Organic Fertilizer) - Aditama, Dhimas; Nurainun, Tengku; Lubis, Fitriani Surayya; Nofirza, Nofirza; Anwardi, Anwardi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2026)
This study evaluates the inventory management of boiler ash raw materials in an independent organic fertilizer company, UMTR Belilas, using the Min-Max method supported by forecasting. The main problem in this study is that consumer demand is often not met on time due to suboptimal inventory management. The purpose of this research is to maintain the availability of raw materials in order to meet consumer demand optimally while reducing the risk of out-of-stock and overstocking. The results show that the application of the Min-Max method results in a minimum stock limit of 88.5 kg and a maximum stock of 171 kg, with an optimal purchase quantity of 82.5 kg per order. The safety stock level is calculated at 6.1 kg, while the Reorder Point (ROP) is set at 88.5 kg. With an order frequency of 120 times per year, this method has succeeded in optimizing storage costs through faster stock turnover. The combination of the Min-Max method and forecasting has proven to be effective in responding to fluctuations in demand, ensuring the availability of raw materials on time, and supporting the operational sustainability of organic fertilizer production.